Selecting for food-feed traits in desi and kabuli genotypes of Chickpea (Cicer arietinum) - Wamatu, Jane; Alemu, Tena; Tolera, Adugna; Beyan, Mohammed; Alkhtib, Ashraf; Eshete, Million; Ahmed, Seid; Rischkowsky, Barbara A. (Journal of Experimental Biology and Agricultural Sciences, 2017)
The study explored the genetic and environmental variability in chickpea for food-feed traits.Seventy nine genotypes of 17 early-maturing desi genotypes, 19 early-maturing kabuli genotypes and 43 latematuring kabuli genotypes were evaluated for food-feed traits in 7 trials laid out in a randomized complete block design in 3 locations in Ethiopia.All trials showed wide genotypic ranges in various traits related to grain yield, straw yield and straw quality.Analysis of variance for individual trials showed significant (P<0.05)effects of genotype, location and their interaction on grain and straw yields, CP, IVOMD and NDF in all populations.Correlation analysis exhibited either positive or insignificant correlations with straw yield in all trials.The correlation between IVOMD and grain yield was insignificant in all trials.Grain yield correlated significantly (P<0.001) and positively to NDF in early maturing kabuli, however, the correlation was moderate (r= 0.396).Grain yield correlated either weakly or insignificantly to CP and Ca in the trials.The correlation between P and grain yield was ignored as the straw content of P was very small in all genotypes (<1.78 g/kg).Weak or absence of correlations between grain yields with straw traits would enable chickpea breeders to manipulate grain yield and straw traits independently.This presents an opportunity to identify parental genotypes for improving grain yield and straw traits for individual locations.